2008
DOI: 10.1039/b815061c
|View full text |Cite
|
Sign up to set email alerts
|

A high sensitive and specific QDs FRET bioprobe for MNase

Abstract: We used CdSe/ZnS quantum dots-ssDNA-fluorescent dye conjugates as bioprobes to detect micrococcal nuclease with high specificity and sensitivity, and further utilized the bioprobe to monitor the micrococcal nuclease activity in the culture medium of Staphylococcus aureus by fluorescence microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 34 publications
0
45
0
Order By: Relevance
“…With the addition of DNase I, FRET decreased from digestion of the duplex DNA and loss of the FRET acceptor. Huang et al reported a similar strategy for sensing micrococcal nuclease (MNase) activity (Huang et al 2008). Streptavidin-coated CdSe/ZnS QD550 was assembled with a DNA probe that was biotinylated at one terminus and labeled with 6-carboxy-X-rhodamine (ROX) at the opposite terminus.…”
Section: Nuclease Assaysmentioning
confidence: 99%
“…With the addition of DNase I, FRET decreased from digestion of the duplex DNA and loss of the FRET acceptor. Huang et al reported a similar strategy for sensing micrococcal nuclease (MNase) activity (Huang et al 2008). Streptavidin-coated CdSe/ZnS QD550 was assembled with a DNA probe that was biotinylated at one terminus and labeled with 6-carboxy-X-rhodamine (ROX) at the opposite terminus.…”
Section: Nuclease Assaysmentioning
confidence: 99%
“…CdSe/ZnS-Ab complex was prepared similar to the previous report [27]. Anti-ABA antibody used in the reaction was in 6 times excess over CdSe/ZnS.…”
Section: Preparation Of Cdse/zns-antibody (Cdse/zns-ab) Complexmentioning
confidence: 99%
“…The hydrophobic CdSe/ZnS QDs were prepared according to the method described previously [35]. In a typical synthesis, 0.0254 g CdO and 0.2280 g stearic acid were put into a three-neck flask.…”
Section: Preparations Of Hydrophobic Cdse/zns Qdsmentioning
confidence: 99%